THE EFFECT OF ORGANIZATIONAL CLIMATE ON PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE (CASE STUDY ON PERUM JASA TIRTA I (ASA)MALANG) - Errica Dwitanti; Sopiah (Bajang Institute, 2022)
Perum Jasa Tirta I (Asa) Malang is a drinking water company owned by the local government. With the increasing number of employees, the conflict of human resources faced by the company is increasingly complex. Therefore the management of human resources must be managed and possible to make the origin of human resources satisfied and satisfactory for the company. Realizing the importance of employee job satisfaction in supporting the company's high productivity, the primary battle in this study is to analyze the source that hypnotizes the job satisfaction of permanent employees at Perum Jasa Tirta I (Asa) Malang. This study aimed to determine the influence of organizational climate and job satisfaction on employee performance and whether job satisfaction can be a variable intervention between corporate environment and employee performance. This study uses quantitative research methods with a descriptive approach. Respondents from this research are the entire staff of Perum Jasa Tirta I (Asa) Malang. The scale used in this study is the Likert scale